Lanscape Element Identification on Tourism Site Parking Area in Bengkulu City to Reducing Urban Temperature - Seftyarizki, Debby; Nugroho, Mohammad Nur Dita; Bahri, Samsul (Jurnal Arsitektur Lansekap; Vol. 10, No. 1 April 2024, 2024)
As an open space, parking area have potential to reducing the urban temperature in micro scale through its landscape elements, especially the softscape and vegetations. This study will identify the potential of 2 tourism parking areas in Bengkulu city in contributing to reducing urban temperature through their landscape elements arrangement. Site observation was conducted to collect all landscape physical elements, as well as vegetation (trees) dimension which then will be simulated through ecotect software to calculate the shadow area. Result of the study showed that landscape condition in both of parking area is in good condition but does not have the potential in reducing urban temperature. It can be happened because the shading area provided from the arrangement of big trees in both parking areas is still deficient. However, Pantai Panjang BIM parking area have a bigger chance in reducing urban temperature if some softscape elemenst were added and other hardscape elements were equipped to be a well design landscape for parking area.